NOÇÕES BÁSICAS DE CÉLULAS-TRONCO - Soares, Maria Fernanda Oliveira; Martins, Caroline Thérèse Aygadoux; Wunder, Eduarda Martins (Salão do Conhecimento, 2018)
Projeto de Iniciação Científica realizado no curso Ciências Biológicas da Unijuí.